Universal Celestial Symbols in the Love Poems of Niyi Osundare and William Shakespeare - AKPOTI, Phyllis Oniopusaziba (Àgídìgbo: ABUAD Journal of the Humanities, 2025)
Niyi Osundare is often praised for his love of nature and for speaking for the earth as his evergreen mistress. However, less attention has been paid to his use of universal symbols in his love poems, just as similar symbolic patterns in the love poetry of William Shakespeare have not been sufficiently examined in comparative terms. This study analyses the use of universal celestial symbols such as the sun, moon, and stars in selected love poems by Niyi Osundare and William Shakespeare. It aims to show how these symbols are employed to convey the theme of love and to invite readers into a shared experience of emotion and meaning. The research is carried out through a close reading of selected poems from Tender Moments (2006) and Complete Sonnets (1906/1991), using Sigmund Freud’s psychoanalytic theory of the unconscious and desire (1900) as the analytical framework. The study finds that universal celestial symbols play a central role in articulating love, desire, and emotional attachment, while also fostering a strong connection between the poets and their readers. It therefore concludes that the use of universal celestial symbols enables both poets to strengthen their thematic concerns, reflect their distinct cultural backgrounds, and encourage deeper reader engagement with their creative expressions.